Religiousness, well-being and ageing – selected explanations of positive relationships - Woźniak, Barbara (Anthropological Review, 2015)
According to research that have been conducted in the field of gerontology, sociology and psychology of ageing, there is a relationship between the level of religious involvement and health status/well-being/quality of life in older age. How does religiousness influence aging process and health status? The aim of the article is to review explanations of a positive relationship between religiousness and health that are discussed in the literature. Those explanations may be grouped in three broad categories reflecting three functions of religion that play a role for well-being in older age. Those functions are: (1) religiousness as a source of coherence and the role of religious coping and provision of meaning in dealing with stressful life events (including ageing losses) (2) religiousness as a source of positive self-perception and a sense of personal control, (3) provision of social resources (i.e. social ties and social support) within religious community and emphasis on interpersonal relations (with special focus on forgiveness as a norm in interpersonal relations). Those functions of religion are discussed in the context of their potential role in successful ageing, as determined by – among others – active engagement in life.